The Use of ChatGPT among Arabic Language and Literature Students: Opportunities and Challenges - Robbani, A. Syahid; Atmantika, Zanuwar Hakim; Bhavani, Sakila Ghina Athifa Eka (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
The use of AI-based chatbots such as ChatGPT offers great potential to improve the learning experience, including for Arabic Language and Literature students. On the other hand, the use of ChatGPT can also lead to excessive dependence on technology, thereby ignoring other learning sources and even ignoring academic morals and ethics. Therefore, this research aims to explore the use of ChatGPT among Arabic language and literature students, with a focus on the opportunities and challenges faced. This type of research is field research using a qualitative approach. Researchers conducted in-depth interviews as a data collection technique. The data obtained was then analyzed through three stages, transcribing data, member checking, and coding. The research results show that Arabic language and literature students use ChatGPT more for their assignment needs, especially assignments related to papers writing. Apart from that, they also use ChatGPT to find out about Arabic literary theories and the writers with their biographies, generate creative ideas, translate texts, look for references and thesis themes, and even use ChatGPT as a discussion partner. But unfortunately, they have not maximized ChatGPT as a medium to strengthen their Arabic language skills. The ability to validate information obtained via ChatGPT is also a very important issue so that students obtain reliable and accountable knowledge.